If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + -4x = 3x + 6 Reorder the terms: 90 + -4x = 6 + 3x Solving 90 + -4x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 90 + -4x + -3x = 6 + 3x + -3x Combine like terms: -4x + -3x = -7x 90 + -7x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 90 + -7x = 6 + 0 90 + -7x = 6 Add '-90' to each side of the equation. 90 + -90 + -7x = 6 + -90 Combine like terms: 90 + -90 = 0 0 + -7x = 6 + -90 -7x = 6 + -90 Combine like terms: 6 + -90 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 5=x^2-4x | | 0.09x^2-1.62x+4.05=0 | | (r+4)=0 | | (t+36)(t+25)=0 | | r^2+7r-78=0 | | 49v^2-16=0 | | x^2+11x+17= | | 20m^2-7m-3=0 | | 4x^3+32x^2+4x+32= | | 4b^2+15b-4=0 | | x*x=-15 | | x*x=15 | | 12-9x=104-37x | | 4x+10=-26-8x | | 0.5x+11=x | | A-13=9 | | 5z^2+25z-az-5a=0 | | 2(z*7)=28 | | 5(x+3)=2(x+3) | | 5x-10=x+46 | | 70=(2+x)(x)(2) | | 288=(2+x)(x)(6) | | x^3-8x^2-x=0 | | 4x+11=43 | | 288=lwh | | 0.5x+15=x | | x+25=y^3+2y^2 | | 7x^2+24x^2=150 | | (x-7)(4x+9)=0 | | -x^2+9x-8=0 | | (5x+1)+4=80 | | x+2(5x+2)= |